2014
DOI: 10.1063/1.4895542
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular interactions in highly concentrated protein solutions upon compression and the role of the solvent

Abstract: The influence of high hydrostatic pressure on the structure and protein-protein interaction potential of highly concentrated lysozyme solutions up to about 370 mg ml(-1) was studied and analyzed using small-angle X-ray scattering in combination with a liquid-state theoretical approach. In the concentration region below 200 mg ml(-1), the interaction parameters of lysozyme solutions are affected by pressure in a nonlinear way, which is probably due to significant changes in the structural properties of bulk wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…As seen in Figure , a significant reduction of the mean squared displacement of H‐atoms occurs already at rather low pressures of a few hundred bars for lysozyme in bulk water solution, suggesting a loss in protein mobility that follows a change in the local energy landscape upon the increase in packing density. This trend is lifted at ≈2 kbar, which is probably due to a solvent‐mediated effect, suggesting a correlation between pressure effects on the structure of water and the internal H atom mobility of the protein. More detailed studies are needed to be able to disentangle the various dynamic modes affected.…”
Section: Conformational Fluctuations and Substates Of Proteinssupporting
confidence: 53%
“…As seen in Figure , a significant reduction of the mean squared displacement of H‐atoms occurs already at rather low pressures of a few hundred bars for lysozyme in bulk water solution, suggesting a loss in protein mobility that follows a change in the local energy landscape upon the increase in packing density. This trend is lifted at ≈2 kbar, which is probably due to a solvent‐mediated effect, suggesting a correlation between pressure effects on the structure of water and the internal H atom mobility of the protein. More detailed studies are needed to be able to disentangle the various dynamic modes affected.…”
Section: Conformational Fluctuations and Substates Of Proteinssupporting
confidence: 53%
“…it is stable. The shape of the scattering curve at high q-values is typical for lysozyme (Grobelny et al, 2014). At low q-values an upturn in the slope of the intensity can be seen, indicating protein aggregation.…”
Section: Resultsmentioning
confidence: 81%
“…From the Guinier approximation the respective radii of gyration can be derived: (1.3 AE 0.1) nm and (3.8 AE 0.4) nm. Lysozyme has been reported to have a radius of gyration of 1.4 nm (Grobelny et al, 2014;Svergun et al, 1998). Thus, it can be concluded that the small objects are single lysozyme molecules whereas the larger objects with a radius of gyration of 3.8 nm are most likely aggregates of lysozyme that form due to the high concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is expected to be suc-cessively filled upon compressing water and aqueous solutions, which is key to the present investigation. For instance, there is solid evidence from experiments that the local solvation shell structure around biomolecules is strongly altered upon compressing such solutions to high hydrostatic pressures (HHP) in the kilobar regime [26][27][28][29][30][31] , which might be depicted as squeezing the second solvation shell into the first one; note that 1 kbar corresponds to 100 MPa. Therefore, understanding the effect of HHP perturbations on the H-bond network of liquid water and its impact on the solvation shells of molecular solutes is increasingly investigated using both experiment and simulation 14,17,18,28,[30][31][32][33][34][35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%